2022
DOI: 10.3390/educsci12100722
|View full text |Cite
|
Sign up to set email alerts
|

Factors Constraining Teachers’ Wellbeing and Agency in a Finnish University: Lessons from the COVID-19 Pandemic

Abstract: The COVID-19 pandemic forced teachers to undergo a sudden shift toward technology-enhanced teaching and learning, challenging their capacities for change in many ways. This study explores those factors constraining teachers’ wellbeing and agency that influenced their capacities as teachers in a Finnish university during the first year of the pandemic. Two sets of data were collected, with an online survey in the spring (n = 297) and autumn (n = 246) of 2020. At both times, challenges with workload, time manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…This meant that what would have been conducted at the university had to be performed at home because of the pandemic. This change caused an increased workload for both teachers and students [18,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…This meant that what would have been conducted at the university had to be performed at home because of the pandemic. This change caused an increased workload for both teachers and students [18,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…However, insufficient computer labs and power outages have become significant challenges before the COVID outbreak [57]. The biggest concern during the post-COVID era was the unavailability of technology at home [54,73]. Further, teachers complained about the inadequate technical equipment during post-COVID, emphasising the limitation of the existing equipment for a successful and continuous online delivery [65].…”
Section: Lack Of Infrastructure and Resourcesmentioning
confidence: 99%
“…The studies concluded the time constraint differently during the post-COVID period. According to teachers, shifting to online platforms added an extra workload [35,36,40,48,73]. The findings of Thumvichit [40], Wang [48], and Mohammad Freihat [36] specifically noted the teacher's lack of interest in exploring new technological features due to the time required in exploring and preparing.…”
Section: Workload and Time Constraintsmentioning
confidence: 99%
See 2 more Smart Citations